1992
DOI: 10.1161/01.cir.86.4.1099
|View full text |Cite
|
Sign up to set email alerts
|

Sex-associated differences in left ventricular function in aortic stenosis of the elderly.

Abstract: Background. In aortic stenosis, the response of the left ventricle to pressure overload varies from compensated hypertrophy to overt heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
218
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(247 citation statements)
references
References 39 publications
26
218
2
1
Order By: Relevance
“…However, this stability of major hemodynamic features of hypertension across a wide range of age appeared to be attained by different patterns of LV adaptation in women and men. Among women, the age-related increase in systolic blood pressure was offset by increasing LV wall thicknesses and mass, similar to the pattern observed previously with aortic stenosis, 33 with no change in measures of LV endocardial or midwall shortening. In contrast, hypertensive men showed no association between age and LV geometric variables, whereas age was positively associated with LV endocardial and midwall shortening both as absolute values and after adjustment for end-systolic stress.…”
Section: Discussionsupporting
confidence: 84%
“…However, this stability of major hemodynamic features of hypertension across a wide range of age appeared to be attained by different patterns of LV adaptation in women and men. Among women, the age-related increase in systolic blood pressure was offset by increasing LV wall thicknesses and mass, similar to the pattern observed previously with aortic stenosis, 33 with no change in measures of LV endocardial or midwall shortening. In contrast, hypertensive men showed no association between age and LV geometric variables, whereas age was positively associated with LV endocardial and midwall shortening both as absolute values and after adjustment for end-systolic stress.…”
Section: Discussionsupporting
confidence: 84%
“…Krumholz et al [23] showed sex differences in patients with systolic hypertension; men demonstrated maladaptive remodelling with left ventricular dilation and eccentric left ventricular hypertrophy in comparison with more "adaptive" remodelling with concentric hypertrophy and small cavity size in women. Similarly, more marked left ventricular hypertrophy, with small cavities, lower end-systolic wall stress and better preservation of left ventricular ejection performance, has been reported in women compared with men with aortic stenosis [24]. Therefore, it is possible that maladaptive remodelling may be more frequent in men, contributing to their higher mortality.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have identified sex-related differences in cardiac structure and function, with men having higher LV mass 5 and worse systolic [7][8][9] and diastolic function 27,28 than women. Our study is the first to demonstrate that sex also influences regression of LV hypertrophy in a large sample of hypertensive patients with a high prevalence of LV hypertrophy at baseline who were treated in a systematic fashion by structured, blinded drug regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented sex-related differences in adaptation to chronic pressure overload, [6][7][8] with women having a tendency towards concentric geometry (ie, increased RWT). We have recently shown in a smaller study that hypertensive patients with concentric LV geometry had greater LV mass reduction after 12 months of antihypertensive therapy than those with normal LV geometry or Sex-related difference in LVH regression JN Bella et al eccentric LV hypertrophy.…”
Section: Female Sex and LV Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation